Comparison of Outcomes of IVF Cycles Between Transferred Frozen Thawed Embryos and Fresh Embryos by a 2 Year Survey - E Shahrokh Tehraninejad; Z Vosoog; F Farajzadeh-Vajari (JRI, 2017)
Background: Infertility as one of most concerning topics in childbearing age mothers needs better managements with less complications and IVF can be assumed as an efficient method. This study aimed to compare pregnancy outcomes in fresh and frozen embryos transferred in IVF cycles. Methods: In a retrospective study, 11201 patients underwent IVF cycles from 21st March 2013 to 20th March 2014 and they were categorized into two groups according to age, previous tubal disease and surgery, tubal ligation, and previous ectopic pregnancy variables. Clinical pregnancy, ectopic pregnancy, multiple pregnancy, spontaneous abortion and preterm labor rates were compared in both groups. Results: 11201 patients were categorized in two groups. Results of 4149 frozen-thawed embryo transfer cycles showed 1281 clinical pregnancies (30.9%) and 7052 fresh embryo transfer cycles which led to 2085 clinical pregnancies (29.6%) without significant differences between groups (p=0.14). Ectopic pregnancy rates in frozen and fresh groups were 38 (3%) and 52 (2.5%), respectively (p=0.409). Spontaneous abortion rates in frozen and fresh groups were 8.4% and 9.4%, respectively (p=0.32).  Preterm labor was seen in both frozen and fresh groups as 28.2% and 23.4%, respectively (p=0.002) and finally, multigestational pregnancy rate was 25.7% and 22.8% in frozen and fresh groups (p=0.06). Conclusion: According to this study, frozen and fresh embryo transfer cycles were not significantly different in clinical pregnancy, ectopic pregnancy, multigestational pregnancy rates, but preterm labor was dominant in frozen group, which should not be overlooked.